Adaptive robotic deburring of die-cast parts with position and orientation measurements using a 3D laser-triangulation sensor - Kosler, Hubert (Strojniški vestnik, 2016)
A system for adaptive robotic deburring with a correction of the errors in workpiece positioning is presented. The correction is based on 3D measurements of the workpiece's surface and its registration to the target surface, measured on a reference workpiece. The surface measurement is performed with a laser-triangulation profilometer. The reference tool path is determined using robot teaching on the reference, already deburred, workpiece. The positioning errors of the currently processed workpiece are compensated by tool path adaptation in accordance with the registration results by means of rotation and translation. The experiments showed that the average precision of localization is 0.06 mm and the average bias between the true and measured values is 0.23 mm. The developed adaptive system is also applicable in other similar applications where it is difficult to ensure repeatable clamping of the workpiece.
Keywords: adaptivne robotske obdelave; korekcije napake položaja; laserska triangulacija; lokalizacija; razigljevanje